Disaster mitigation and forest preservation in marind-anim literature - Arin Mantara Anggawirya; Lastika Ary Prihandoko; Martha Betaubun; Rosalia Floriani (EduLite: Journal of English Education, Literature and Culture, 2023)
This paper analyzes the myths of the marind-anim community and the representation of nature in these myths through an eco-literacy approach. The eco-literary approach is a method used in investigating nature representation through a literary work. The eco-literary approach aims to bring the new perspective of having a literary work, it focuses on the idea of how the environment and the interaction of the characters toward the environment. The use of the literary work as the Marind-Anim fundamental belief in intervening the policy can be powerful, therefore In this research, the literary work will be specified into the oral literature since Marind-Anim did not have any written literature. In verifying the findings and their relation to ancestral beliefs. Through the representation of nature that emerged in the myths of the marind anim community, two main findings were obtained, namely the awareness of disaster mitigation and figures of Dema in myths who have a major role in teaching about balancing the use of natural resources. The findings on the potential of the Dema figure who appears as a forest guardian figure can be continued as a role model or figure in raising the awareness of forest conservation and can be used as a means of making policy through campaigning forest guards in literary works.